2000
DOI: 10.1093/jnci/92.23.1881
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Gastric Dysplasia: Randomized Trial of Antioxidant Supplements and Anti-Helicobacter pylori Therapy

Abstract: In the very high-risk population studied, effective anti-H. pylori treatment and dietary supplementation with antioxidant micronutrients may interfere with the precancerous process, mostly by increasing the rate of regression of cancer precursor lesions, and may be an effective strategy to prevent gastric carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
451
2
22

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 627 publications
(491 citation statements)
references
References 23 publications
16
451
2
22
Order By: Relevance
“…Several studies have reported annual incidences of MGC after H. pylori eradication, ranging from 0.1 to 0.5 % in healthy individuals or peptic ulcer patients [26][27][28][29][30][31][32][33], and from 0.8 to 4.1 % in patients after endoscopic resection for early gastric cancer [9,[11][12][13][14][15]. Individuals after endoscopic resection had a higher risk of MGC compared with those who were healthy or had peptic ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported annual incidences of MGC after H. pylori eradication, ranging from 0.1 to 0.5 % in healthy individuals or peptic ulcer patients [26][27][28][29][30][31][32][33], and from 0.8 to 4.1 % in patients after endoscopic resection for early gastric cancer [9,[11][12][13][14][15]. Individuals after endoscopic resection had a higher risk of MGC compared with those who were healthy or had peptic ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not observe any association with plasma levels of a-or b-carotene and GC risk, whereas previous prospective studies have shown lower plasma levels of b-carotene in GC cancer cases vs controls in a Western population (Eichholzer et al, 1996) and either an inverse association (Yuan et al, 2004), no association or a positive association (You et al, 2000) with GC risk in high-risk Chinese populations. Intervention studies with b-carotene, however, have shown no effect on GC risk in low-risk populations (Hennekens et al, 1996), and either no effect (Varis et al, 1998) or mild protective effects in high-risk populations (Blot et al, 1995;Correa et al, 2000). In the present study, no GC risk associations were observed for dietary b-carotene and in a concurrent study of fruit and vegetable intake based on the entire EPIC cohort, no GC risk association was observed with the intake of fruiting and root vegetables , which are good sources of carotenes (Al Delaimy et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…Ingesta de compostos nitrogenados, dieta rica em sal e pobre em frutas, verduras e vitamina C, bem como tabagismo e ocorrência de refluxo biliar parecem estar relacionados a maior ocorrência de lesões pré-neoplásicas e câncer gástrico (9,18,19,25,42,43) .…”
Section: Discussionunclassified